A Development of a Mobile Application for Baby Food Journey - Alias, Nurul Farhana; Marjudi, Suziyanti (Applied Information Technology And Computer Science, 2022)
Baby Food Journey Mobile Application is aimed to provide user recipes and information that suits the baby’s age. By using this mobile application, the user also can create a meal plan and track the baby’s food journey easily. This application is developed due to the problems faced by many new parents or guardians who are not able to figure out what to give to the baby when they started to wean and afterward. Plus, searching for the recipes and information about baby’s food in a manual way such as reading a book and surfing the internet is time-consuming. Although there are existing applications that offer user to search baby recipes, it does not have a variety of functions. This becomes a problem for working parents or guardians to search for recipes and create a meal plan for the baby at the same time. Thus, this application is going to overcome the limitations by offering multi-function features. The project will be designed by using an object-oriented approach and prototype model as its methodology. Software that will be used in this project are Android Studio and Firebase Database. This application is expected to allow authorized users to access the features included in the system without any errors. With the application, hopefully, it can help to ease the user to search recipes or information besides conveniently creating baby’s meal plan. Baby Food Journey Mobile Application will become an effective way for concerned guardians out there to provide nothing but the best food for the little ones.